A chronology of aviation a day-by-day history of a century of powered flight - Winchester, Jim (World history timeline, 2013)
This innovative volume explores the fascinating history of aviation, from early developments, through the technological advances of two world wars, to modern-day marvels such as the A-380 and stealth fighter jets. While giving an overview of all aviation history, 'The Chronology of Aviation' also allows major period of advance such as World War II to be covered in detail